Autopercepção em saúde, saúde bucal e qualidade de vida em pessoas transgêneras de um município da região central do Rio Grande do Sul - Silva, Layanne Almeida da (2022)
Understanding the diversity of gender identity is essential for health services and professionals to be aware of the demands and specificities of this group, thus providing better reception and qualified listening. Therefore, the objective of this study was to know the self-perception of health, oral health and quality of life of people who identify as transgender in a city in the Central Region of Rio Grande do Sul. This is a descriptive exploratory qualitative study, the sample consisted of 10 self-declared transgender participants, over 18 years old. The capture of participants was through the “snowball” method, we started contact with trans people who had visibility in the Municipality and with the services that serve this group. This study was approved by the Research Ethics Committee of the Federal University of Santa Maria. And the participants were informed of the objectives of the study and signed the Informed Consent Form. The results suggest a perception of health as biomedical, focused on access to services and medicines, oral health as a factor that produces self-esteem and an improvement in the quality of life with the gender transition, improving self-care. This study contributed to understanding the perception, experiences and experiences of trans people living in the Central Region of Rio Grande do Sul. Training sessions were held for dentists in the Municipality Network, in addition to discussions on gender issues in a research group. It was important to equip health professionals and academics to understand the uniqueness of this population. In addition, permanent education proved to be necessary in view of the particularities that are being understood through recent studies and that will still be understood by future studies that are fundamental for the reorganization of Public Policies, Network flows and professional updates.